2017
DOI: 10.17352/ojps.000007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aqueous Extracts of Green Tea in Arsenic induced Toxicity in Mice

Abstract: Ground water arsenic contamination is a global problem affecting thousands of people worldwide, thus present study was aimed to evaluate the hypothesis that green tea extracts, having high polyphenolic content, might be able to combat the oxidative cellular damage caused by arsenic toxicity and to prevent further development of free radicals.In the present study treatment groups received sodium arsenite orally at the dose of 3 mg kg-1 body weight daily for 4 weeks followed by administration of Camellia sinensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Tea, which has become a dietary component of Indians, consumed as a most popular beverage, has also shown arsenic toxicity mitigating effects. Studies have reported DNA repair, genoprotective action of green tea, as well as black tea by affecting DNA repair enzymes such as DNA ligase 1/4, PARP1, ERCC1/2, and DNA polymerase beta in in vitro and in vivo studies along with ameliorating ROS levels through an antioxidant mechanism, affecting liver and kidney functions . The principle active component of green tea, epigallocatechin gallate, has also shown potential genoprotective, antioxidant, and free radical scavenging actions in an in vivo study .…”
Section: Phytochemicals and Their Use To Manage Arsenic Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Tea, which has become a dietary component of Indians, consumed as a most popular beverage, has also shown arsenic toxicity mitigating effects. Studies have reported DNA repair, genoprotective action of green tea, as well as black tea by affecting DNA repair enzymes such as DNA ligase 1/4, PARP1, ERCC1/2, and DNA polymerase beta in in vitro and in vivo studies along with ameliorating ROS levels through an antioxidant mechanism, affecting liver and kidney functions . The principle active component of green tea, epigallocatechin gallate, has also shown potential genoprotective, antioxidant, and free radical scavenging actions in an in vivo study .…”
Section: Phytochemicals and Their Use To Manage Arsenic Toxicitymentioning
confidence: 99%
“…Studies have reported DNA repair, genoprotective action of green tea, as well as black tea by affecting DNA repair enzymes such as DNA ligase 1/4, PARP1, ERCC1/2, and DNA polymerase beta in in vitro and in vivo studies 79 along with ameliorating ROS levels through an antioxidant mechanism, 80 affecting liver and kidney functions. 81 The principle active component of green tea, epigallocatechin gallate, has also shown potential genoprotective, antioxidant, and free radical scavenging actions in an in vivo study. 82 The efficacy of green tea has been reported to be beneficial in reducing deleterious effects of arsenic in view of its antioxidant potential and antitumorigenic effect, which participates in various stages of carcinogenesis.…”
Section: Phytochemicals and Their Use To Manage Arsenic Toxicitymentioning
confidence: 99%